An Overview and Assessment of Performance of the Central American Presidential Summit. (10th May 2019) - Parthenay, Kevin
Abstract : This article evaluates the performance of the Central American Presidential Summit, based on a political sociology approach of regionalism, and the concepts of political authority and rules compliance. The trajectory of the Presidential Summits since 1986, is examined through a theoretical approximation inspired by international relations sociologists and by applying an inductive methodology. The results indicate that almost since its creation, the Central American Presidential Summit did not achieve full operability according to its institutional design and diplomatic practices. The evidence suggests that presidential summits do not act as the driver of Central American regionalism. The article affirms that the weak political will from the member states explains the limited institutional performance of the Central American Integration System.